Development of Power Operated Coconut Dehusker - PATIL, S. R.; SHAHARE, P. U.; AWARE, V. V.; SHIRSAT, N. A. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
Dehusking is the process of removing the outer covering called husk from the coconut to get two important commercial products such as copra or dried kernel and fibers or coir. Dehusking constitutes the most difficult and tedious operation in the processing of coconut. Traditional methods of dehusking are quite time consuming as well as involve risk. Manual dehusking is not only hard and dangerous but requires considerable skill, strong wrist and arm. Motorized and hydraulic coconut dehusking machine are commercially available in market but cost of this machine is a limiting factor. A low cost, medium speed coconut dehusker is developed at Dr. Balasaheb Sawant Konkan Krishi Vidyapeeth, Dapoli. It consists of main frame, electric motor, gear box, cam and follower, lifter, holding mechanism and splitting mechanism etc. The power from electric motor was transmitted to gear box. The coconut is fitted in two jaws, developed for holding nuts both side. The cam fitted on gear box shaft operates lifter and blade for cutting coconut at outer periphery. Coconut has to rotate by operator for 3-4 cuts on coconut periphery to loosen husk. The performance evaluation was carried on the basis of dehusking time, output capacity, dehusking efficiency and operating cost etc. The machine is able to dehusk any shape and sizes of coconut without nut breakage. The average dehusking time required to dehusk one coconut was 30.6 sec and output capacity was 118 nuts per hours, which is 40 per cent higher than the manual dehusker. The average dehusking efficiency of developed power operated dehusker was 96.62 per cent. The cost of fabrication of machine was Rs. 13882 and total operating cost for dehusking for one coconut was Rs. 0.32 per coconut.